Diary of a Tokyo teen : a Japanese-American girl travels to the land of trendy fashion, high-tech toilets and maid cafes - Inzer, Christine Mari, 1997- (Tuttle Publishing, 2016)
Illustrated, comic-style memoir detailing the experiences of a sixteen-year-old girl with one Japanese and one American parent on her first trip back to Japan after her birth. Discusses differences in culture, food, style, and time spent with her extended family.